NAMANGAN WÁLAYATÍ KENAGAS QARAQALPAQLARÍ - Prekeeva, A.A. (ILIM hám JÁMIYET, 2024)
This article is devoted to the issues of everyday life, history and dialect of the Karakalpaks living in the rural assembly of citizens «Kenagas» of the Pap district of the Namangan region.